Variational approach and exact solutions for a generalized coupled Zakharov–Kuznetsov system. (1st March 2017) - Porogo, O.P.; Muatjetjeja, B.; Adem, A.R.
Abstract: In the present paper, we obtain a variational principle for a generalized coupled Zakharov–Kuznetsov system, which does not admit any Lagrangian formulation in its present form. The eminent Noether's theorem will then be employed to compensate for this approach. In addition, exact solutions will be constructed for the generalized coupled Zakharov–Kuznetsov system using the Kudryashov method and the Jacobi elliptic function method.